Branding. Does its approach and applicability follow a one-dimensional trend? Critical analysis from a systematic review of the last 10 years. - Alberto, Vargas-Merino Jorge; Armando, Rios Lama Cristian (The journal of contemporary issues in business and government, 2021)
Branding has become one of the most relevant marketing concepts because of the importance and benefits of strategically developing a brand. However, it is commonly categorized in the business environment, which limits its applicability. In view of this, this research work seeks to analyze the various approaches and practical applications of branding in the last 10 years. 137 scientific articles were consulted using various scientific databases, and 54 were finally extracted, 49 of which were of the highest academic level. To be included, an article had to have relevant, current, reliable information related to the topic in question. The growing importance of branding in the business sector has caused many scholars to choose to extrapolate branding principles to different areas, but the full implications of branding are not yet known. Both its relationship with an ancestral concept such as anthropomorphization, and its relationship with state-of-the-art technologies such as virtual reality or the Internet of things, or the incredible capacity of being able to mitigate an individual's physical pain through the creation of emotional bonds, have not yet been widely studied by the scientific marketing community.